Comparative Analysis of Battery SOC Depletion and Driving Range of PMSM-driven Electric Vehicle (EV) using Sinusoidal PWM (SPWM) and Space Vector PWM (SVPWM) Control - Khin Maung San; Swe, Wunna (The Indonesian Journal of Computer Science, 2025)
Conventional vehicles utilize fossil fuels to provide a good performance and long range leading to exhaust gas emissions causing environmental pollution & low fuel economy. Electric vehicles are called future vehicles in the place of internal combustion engines because they work with pollution and are more efficient. In the impending future, the automotive industry is marching towards cleaner energy. This paper presents the comparative analysis of battery SOC and driving range of an electric vehicle (EV) with a decoupling control method using SPWM and SVPWM. Simulation tests have been carried out on an 80 kW Nissan Leaf EV that consists of a permanent magnet synchronous motor and a three-level inverter. The analysis is focused on MATLAB simulations, based on speed regulation, torque response, usage battery SOC, and travel range. For these closed-loop feedback control methods, the reference speed is obtained by driving an internal combustion engine (ICE) car in the mountain region of Southen Shan State, Myanmar for 60 sec.